Optimasi Keuntungan Toko Buah Menggunakan Linear Programming Melalui Metode Simpleks (Studi Kasus : Toko Buah Sirandorung) - Syahfitri, Diana; Priyanti, Dinda Octa; Pefrianti, Lenni; Syahputri, Tria; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
Fruit stores face the challenge of determining optimal prices to maximize profits while considering stock constraints, costs, and demand. This research uses a linear programming approach with the simplex method to solve this problem. The data used includes reseller prices, selling prices, stock capacity and market demand for seven types of fruit. The manual process with the simplex method was validated using QM for Windows software. The research results show that this method is successful in determining the optimal combination of selling price and production quantity, which provides a maximum profit of IDR 666,000 per day. This approach provides a strategic solution for fruit shop managers in making data-based decisions.